Understanding the relationship between alcohol outlet density and life expectancy in Baltimore City: The role of community violence and community disadvantage. Issue 1 (10th July 2018) - Furr‐Holden, C. Debra M.; Nesoff, Elizabeth D.; Nelson, Victoria; Milam, Adam J.; Smart, Mieka; Lacey, Krim; Thorpe, Roland J.; Leaf, Philip J.
Abstract: This research investigated the relationship between alcohol outlet density (AOD) and life expectancy, as mediated by community violence and community disadvantage. We used linear regression models to assess bivariate and multivariate relationships. There was a negative bivariate association between liquor store density and average life expectancy (β = −7.3370, p < 0.001). This relationship was partially attenuated when controlling for community disadvantage and fully attenuated when controlling for community violence. Bars/taverns (i.e., on‐premise) were not associated with average life expectancy (β = −0.589, p = 0.220). Liquor store density is associated with higher levels of community disadvantage and higher rates of violence, both of which are associated with lower life expectancies. Future research, potential intervention, and current related policies are discussed.